Suicide Screening Tools for Pediatric Emergency Department Patients: A Systematic Review - Scudder, Amanda; Rosin, Richard; Baltich Nelson, Becky; Boudreaux, Edwin D.; Larkin, Celine (Frontiers in Psychiatry, 2022)
BACKGROUND: According to the Centers for Disease Control and Prevention, suicidality and suicidal behavior among youth continues to increase significantly each year. Many of those who die by suicide interact with health services in the year before death. This systematic review sought to identify and describe empirically tested screening tools for suicidality in youth presenting to Emergency Departments (ED). OBJECTIVE: (1) To identify and compare existing tools used to screen for suicidality in children and adolescents who present to the ED and (2) to ascertain the prevalence of suicidality in pediatric populations found with these tools. METHODS: We searched Ovid Medline, CINAHL, Scopus, and Cochrane databases for primary research studies that identified and evaluated screening tools for suicide risk in pediatric ED patients. A total of 7,597 publications published before August 25, 2021 met search criteria and were screened by two independent reviewers based on our inclusion and exclusion criteria, with any conflicts resolved via consensus meetings or an independent reviewer. A total of 110 papers were selected for full text review, of which 67 were excluded upon further inspection. Covidence was used to extract and synthesize results. RESULTS: 43 articles were eligible for inclusion. Most studies (n = 33) took place in general pediatric EDs; the quality was generally high. Patients ranged from 4-24 years old, with most screening tested in patients 12 years and older. The most researched tools were the Ask-Suicide Screening Questions (ASQ) (n = 15), Columbia-Suicide Severity Rating Scale (C-SSRS) (n = 12), Suicidal Ideation Questionnaire (SIQ) (n = 11), and the Risk of Suicide Questionnaire (RSQ) (n = 7). Where screening was applied to all patients, about one-fifth of pediatric ED patients screened positive; where suicide screening was applied to psychiatric patients only, over half screened positive. Positive screens were more likely to be female and older than negative screens and they were more likely to be assessed and admitted. CONCLUSION: Several validated screening tools exist for the purpose of screening pediatric populations in EDs for suicidality. Such tools may help to support early detection and appropriate intervention for youth at risk of suicide.